Implementation of the Wim Hof Therapy in Airway Management and Nursing Education for Respiratory Clinical Symptoms - Denisa Adella; Irman Somantri; Ati Surya Mediawati (Journal of Multidisciplinary Research, 2026)
Airway disorders are common clinical issues among patients with chronic respiratory diseases such as pulmonary tuberculosis, often resulting in ineffective breathing patterns, decreased oxygen saturation, and persistent cough. Nurses play a critical role in airway management, not only through pharmacological therapy but also through non-pharmacological, education-based interventions. One potential method for improving respiratory function is the Wim Hof technique.This study employed a descriptive case study design using the 3M management approach (Man, Material, Method) and the POAC management functions (Planning, Organizing, Actuating, Controlling). The intervention consisted of Wim Hof breathing exercises administered to one pulmonary tuberculosis patient for three consecutive days at a frequency of twice daily. Parameters measured included respiratory rate, oxygen saturation, cough frequency, and sleep quality.Results demonstrated a reduction in respiratory rate from 27x/minute to 20x/minute, a decrease in cough frequency by up to 50%, and an improvement in oxygen saturation from 99% with 5 L/min supplemental oxygen to 97% on room air. Furthermore, the patient’s sleep quality improved, and family engagement in care increased significantly.The implementation of the Wim Hof technique yielded positive effects on respiratory function through enhanced alveolar ventilation, stabilization of oxygenation, and reduced work of breathing. The combined application of the 3M and POAC frameworks strengthened the effectiveness of the intervention by reinforcing the roles of nurses and family members. Wim Hof breathing therapy is effective as part of airway management interventions for nursing diagnoses of ineffective breathing pattern, ineffective airway clearance, and impaired gas exchange.